Decision matrices: Tools to enhance middle school engineering instruction. (2nd January 2017) - Gonczi, Amanda L.; Bergman, Brenda G.; Huntoon, Jackie; Allen, Robin; McIntyre, Barb; Turner, Sheri; Davis, Jen; Handler, Rob
Abstract: Decision matrices are valuable engineering tools. They allow engineers to objectively examine solution options. Decision matrices can be incorporated in K-12 classrooms to support authentic engineering instruction. In this article we provide examples of how decision matrices have been incorporated into 6th and 7th grade classrooms as part of an innovative NGSS-aligned curriculum. The article also provides guidelines and examples for how to scaffold decision matrices to support student and teacher confidence and use.